F. A. Irele, J. T. Birnie, G. Ansre: "The Teaching of Traditional African Literature". Proceedings of the Conference Held at the University of Ghana, Legon (May 5th-8th, 1968) - Uribe-Villegas, Oscar (Revista Mexicana de Sociología, 2024)
-